ショウワキチ ノ ジシン ケンチリツ ジョホウ - 神沼, 克伊; カミヌマ, カツタダ; KAMINUMA, Katsutada (国立極地研究所, 1968)
P(論文) The seismological observation at Syowa Station has been carried out using the HES seismographs We examined how many earthquakes reported in EDR of USCGS were detected as P or PKP phases at Syowa Station (SYO), Antarctica, during the period from March to December in 1967 The detection capability in connection with the magnitude and the epicentral distance was investigated The earthquake detection capability of Syowa Station is 7 percent in the winter season and 2 percent in the summer season These values are the same order as those at the stations of DRV (Dumont d'Urville) and MIR (Mirny), but very low as compared with those of SPA (South Pole Ssation) The further result will be published in the Bulletin of the Earthquake Research Institute departmental bulletin paper